Pengaruh Motivasi dan Psikologis Karyawan Terhadap Kepuasan Kerja di Perusahaan - Mintawati, Hesri; Simangunsong, Bonse Aris Mandala Putra; Suhardi, Mulyadi; Supriyadi, Agung; Efrida, Irma; Louw, Rachmi Febryani (Neolectura, 2023)
Human resources are a very important aspect in a company, with good resources the company can achieve company goals. Employees are human resources who play an important role in implementing the vision, mission and goals of an industry. The aim of the research is to determine the influence of motivation, work environment, psychological climate and job satisfaction on employee performance in a company. Researchers used literature review and descriptive analysis methods. Descriptive analysis is a method by collecting data, compiling or classifying, analyzing and interpreting it. The results of the analysis prove that employee motivation and psychology greatly influence employee job satisfaction in a company. The results of the research have implications for motivation, work environment conditions, psychological climate and employee job satisfaction which need to be improved and if employee job satisfaction increases then employee performance will also increase.